Perspectives on transdermal ultrasound mediated drug delivery - Smith, Nadine Barrie (Dove Medical Press, 2007)
The use of needles for multiple injection of drugs, such as insulin for diabetes, can be painful. As a result, prescribed drug noncompliance can result in severe medical complications. Several noninvasive methods exist for transdermal drug delivery. These include chemical mediation using liposomes and chemical enhancers or physical mechanisms such as microneedles, iontophoresis, electroporation, and ultrasound. Ultrasound enhanced transdermal drug delivery offers advantages over traditional drug delivery methods which are often invasive and painful. A broad review of the transdermal ultrasound drug delivery literature has shown that this technology offers promising potential for noninvasive drug administration. From a clinical perspective, few drugs, proteins or peptides have been successfully administered transdermally because of the low skin permeability to these relatively large molecules, although much work is underway to resolve this problem. The proposed mechanism of ultrasound has been suggested to be the result of cavitation, which is discussed along with the bioeffects from therapeutic ultrasound. For low frequencies, potential transducers which can be used for drug delivery are discussed, along with cautions regarding ultrasound safety versus efficacy.